2004
DOI: 10.3130/jaabe.3.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Incorporation of Sawdust Waste Incineration Fly Ash in Cement Pastes and Mortars

Abstract: This paper presents the result of a study on the use of sawdust waste incineration fly ash (SWIFA) as supplementary cementing materials. Tests on the setting times and strength development of cement paste and mortar with up to 30 percent SWIFA were carried out. Results of the setting times and compressive strengths show that with increasing amounts of SWIFA, the setting times of the paste were extended and the compressive strengths decreased. Pozzolanic activity index of the material was also confirmed to be a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(41 citation statements)
references
References 8 publications
(3 reference statements)
2
34
0
Order By: Relevance
“…Moreover it is possible that part of LOI may be attributed to CaCO 3 in the ash which has been found in other types of ash obtained from agroindustrial waste. In fact calcium carbonate was confirmed by XRD in sawdust ash by 21 and in forest waste ash by 22 . Poykio et al 23 also state that calcium carbonate in a high percentage is typically observed in forest waste ash and that although Loss of Ignition is widely attributed to the amount of combustible matter in the sample (especially for coal fly ash), it may not represent rightly the amount of unburnt carbon in ash but rather the volatile fraction 23 .…”
Section: Chemical and Physical Properties Of Cpamentioning
confidence: 82%
“…Moreover it is possible that part of LOI may be attributed to CaCO 3 in the ash which has been found in other types of ash obtained from agroindustrial waste. In fact calcium carbonate was confirmed by XRD in sawdust ash by 21 and in forest waste ash by 22 . Poykio et al 23 also state that calcium carbonate in a high percentage is typically observed in forest waste ash and that although Loss of Ignition is widely attributed to the amount of combustible matter in the sample (especially for coal fly ash), it may not represent rightly the amount of unburnt carbon in ash but rather the volatile fraction 23 .…”
Section: Chemical and Physical Properties Of Cpamentioning
confidence: 82%
“…According to [20] tests on cement mortar with and without 15% replacement of cement with wood waste fly-ash have shown little effect on water absorption. In another study [27] the increase of wood waste fly-ash from 5% to 30% of binder mass in cement concrete resulted in a less than 1% increase in water absorption.…”
Section: Results Of Density and Water Absorption Testsmentioning
confidence: 99%
“…The wood waste fly-ash influences the setting time. It delays the initial and final setting time of the concrete mix [20,21]. The mechanical properties of cement composites can be enhanced with wood waste fly-ash with the replacement level up to 10% [19].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have analyzed the suitability of wood ash as a partial cement replacement material in the production of structural grade concrete and self compacting concrete for applications in building construction (8,9,10,11). Wood fly ash consists of particles which are highly irregular in shape with a highly porous surface (12 (13).…”
Section: Introductionmentioning
confidence: 99%